CURRENCY COUNTERFEITING AS A TRANSNATIONAL CRIMINAL PHENOMENON AND ITS EFFECTS ON INDIVIDUAL SECURITY - Constantin, Eduard (International Journal of Legal and Social Order, 2026)
Currency counterfeiting is a dynamic criminal phenomenon that is constantly manifested in Romanian society, but also at international level, usually having a transnational and organized character. Organized crime groups operate on the territory of different countries in order to counterfeit national currency, euro currency or other foreign currency and put counterfeit currency into circulation. Currency counterfeiting is one of the main sources of income for organized crime groups. Usually, counterfeit currency are promoted and sold on the „darknet”. Through hidden online trading platforms, counterfeit currency are sold anywhere in the world, with transactions being very difficult to detect. Counterfeit currency are transported, delivered or distributed internationally using courier or postal companies, through parcel services, with counterfeits easily reaching any country in the world. Counterfeit currency are capitalized, transformed into good money, through the purchase of goods, currency exchange or sale, and the profit obtained is reinvested in other illicit businesses (drug businesses, businesses in the sexual services sector) or in apparently legal businesses (establishing commercial companies in tourism or public catering), locally or internationally. From this perspective, currency counterfeiting can have indirect negative consequences on the security of the person, respectively on his life, health, physical, psychological and sexual integrity and freedom, being a means of financing human trafficking and illicit drug trafficking.